(untitled) (Research, Society and Development, 2022)
This article aims to identify the effects of two official programs involving multimedia: ProInfro (National Program for Technologies in Education) and Prouca (One Computer per Student Program) on education. The work is based on a bibliographical research of a qualitative nature, whose data analysis was carried out according to the content analysis of Bardin (2016). The survey and study period took place between September and December 2019. The first program was created in 1997 to disseminate the pedagogical use of computer and telecommunications technologies in schools. The second program is more recent, implemented in 2010 to promote pedagogical digital inclusion and the development of teaching and learning processes. As a result, we can see that both programs have a deficiency in their execution: insufficient teacher training; lack of financial resources for laboratory maintenance; inadequate infrastructure; lack of technical assistance; instrumentalist and technical character and others. Therefore, we consider that just offering schools technological equipment does not translate into significant changes in the educational field. Thus, it is necessary to prepare students to live in today’s society, through programs or projects that promote the inclusion of computers, laptops, internet in schools, but also through quality training for the use of such. This is required nowadays, as technology is present in all aspects of humanity.